A PRIVATE OWNERSHIP BIAS IN TRANSIT CHOICE - Sherman, Roger (American Economic Review, 1967)
THE CONTINUING DEFECTION OF PUBLIC TRANSIT RIDERS IN BIG CITIES SUGGEST THAT EVENTUAL DOMINANCE BY PRIVATE AUTOMOBILES MAY BE INEVITABLE. A CHICAGO SURVEY HAS INDICATED THAT ONLY A VERY LARGE SUBSIDY WOULD PERSUADE A SIGNIFICANT NUMBER OF AUTO TRAVELERS TO SWITCH TO PUBLIC MODES. THERE REMAINS A QUESTION, HOWEVER, WHETHER THE PRIVATE AUTO IS GAINING ASCENDANCY BY GENUINE CONSUMER CHOICE OR BECAUSE PRIVATE COSTS DIFFER SUFFICIENTLY FROM SOCIAL COSTS TO PRODUCE A MISALLOCATION OF RESOURCES IN FAVOR OF AUTOS. A RESOURCE ALLOCATION BIAS CAN FAVOR PRIVATE AUTOS WHEN AN OWNERSHIP COMMITMENT ENCOURAGES AN EITHER/OR CHOICE BETWEEN PRIVATE AND PUBLIC MODES, ASSUMING THAT ALL TRANSIT IS CHARACTERIZED BY DECREASING COSTS, AND THAT PUBLIC TRANSIT MUST COVER ITS COST AND USES SINGLE, CONSTANT PRICES TO DO SO. POSSIBLE MISALLOCATION AMONG THE PUBLIC TRANSIT MODES WAS ALSO DEMONSTRATED. TO COMPENSATE FOR THESE ALLOCATIVE BIASES, A COLLECTIVE INSTITUTION WAS PROPOSED TO IMPLEMENT FIXED AND VARIABLE FEES. THE PROPOSED INSTITUTION WOULD ENABLE EACH CONSUMER TO PLAN HIS TRANSIT USAGE, TAKING ACCOUNT OF APPROXIMATE MARGINAL SOCIAL COSTS, AND ON THAT BASIS MAKE A FORWARD COMMITMENT EITHER TO PRIVATE OR PUBLIC TRANSIT MEANS. IN THIS WAY INVESTMENT IN TRANSIT RESOURCES, AS WELL AS SHORT-RUN USAGE, CAN BE COORDINATED. THE RISE IN ALTERNATIVE TRANSIT MODES MAKE THIS APPROACH MORE APPROPRIATE THAN THE TRADITIONAL REGULATION OF SEPARATE MONOPOLIES. THE ARGUMENT IS RELEVANT PRIMARILY FOR URBAN AREAS, WHERE SUBSTITUTION POSSIBILITIES ARE GREATEST, WHERE NECESSARY ORGANIZING IS MOST FEASIBLE, AND WHERE TRANSIT RESOURCES ALLOCATION PROBLEMS ARE MOST URGENT.